Development of a Religious Character Education Model through the Tahfizh Al-Qur’an Program in Musi Rawas - Sujarwo Sujarwo; Muhamad Akip; Kunalan Kuriaya (GHAITSA : Islamic Education Journal, 2026)
This study explores the development of religious character through the Tahfizh Al-Qur’an program in Musi Rawas, Indonesia. Using a qualitative case study approach, data were collected from program leaders, teachers, and students through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that character formation progresses from externally motivated actions to internalized moral awareness, supported by habituation, teacher exemplification, structured tahfizh activities, and a religious environment. The results align with Lickona’s character education theory, An-Nahlawi’s habituation approach, and Edward III’s policy implementation framework. The study produces a validated, context-specific model for integrating religious values into nonformal education, highlighting that successful character development depends on systematic program implementation and consistent social practice. This model provides practical guidance for enhancing religious character education in nonformal Islamic institutions.